2016
DOI: 10.14814/phy2.12987
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit number estimates and neuromuscular transmission in the tibialis anterior of master athletes: evidence that athletic older people are not spared from age-related motor unit remodeling

Abstract: Muscle motor unit numbers decrease markedly in old age, while remaining motor units are enlarged and can have reduced neuromuscular junction transmission stability. However, it is possible that regular intense physical activity throughout life can attenuate this remodeling. The aim of this study was to compare the number, size, and neuromuscular junction transmission stability of tibialis anterior (TA) motor units in healthy young and older men with those of exceptionally active master runners. The distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 34 publications
4
87
2
1
Order By: Relevance
“…; Piasecki et al . ,b). In the present study, we observed that in non‐sarcopenic and pre‐sarcopenic elderly men, a doubling of motor unit size in TA and a 26–42% higher motor unit size in VL (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…; Piasecki et al . ,b). In the present study, we observed that in non‐sarcopenic and pre‐sarcopenic elderly men, a doubling of motor unit size in TA and a 26–42% higher motor unit size in VL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The motor points of VL (proximal) and TA were identified by low‐intensity percutaneous electrical stimulations as previously described (Piasecki et al . ,b). For VL, the motor point was located along the centre line of the muscle around 220 mm from the lateral femoral condyle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, ; Piasecki et al . ). While denervation changes, consistent with motor neuron losses, were noted in both groups of older women in the current work, biopsies from world‐class masters athletes showed findings of improved reinnervation.…”
mentioning
confidence: 97%